Book review: Conway, G., Badiane, O. and Glatzel, K. 2019: Food for All in Africa: Sustainable Intensification for African Farmers. (January 2021) - Sage, Nick
Conway, G., Badiane, O. and Glatzel, K. 2019: Food for All in Africa: Sustainable Intensification for African Farmers . New York: Cornell University Press. 322 pp. £19.99 paperback. ISBN: 978-1501743887 (paperback).